The Political Economy of Chinese Debt and International Monetary Fund Conditionality. Issue 4 (23rd November 2022) - Kern, Andreas; Reinsberg, Bernhard
Abstract: Developing and emerging market economies have increased their debt exposure to China in recent years. Despite its initial promise, many borrowers of Chinese loans face difficulties in meeting these loan obligations. Under what circumstances do Chinese borrowers in debt distress turn to the International Monetary Fund (IMF)? Our starting point is that Chinese loans are tied into projects that promise to generate sufficient revenue to repay these loans. We expect that governments turn to the IMF for bailout funding when a severe shock erodes the value of the underlying loan collateral, requiring mobilizing revenues and implementing austerity measures. Without alternative financing options, the IMF becomes the most viable option to weather financial distress. We expect governments to accept a 'whatever-it-takes' number of loan conditions. Using cross-country time-series analysis for up to 162 countries between 2000 and 2018, we show that defaults on Chinese debt trigger IMF programs only when a country experiences a severe adverse shock. Countries tapping the IMF also accept a greater number of loan conditions. From a policy perspective, current financial distress in borrowing countries underscores the urgency to design and deploy targeted governance reform measures beyond program safeguards and loan conditions to mitigate the built-up of macro-financial vulnerabilities, independent of where the money is coming from.